2003
DOI: 10.1177/875697280303400407
|View full text |Cite
|
Sign up to set email alerts
|

Project Management in the Age of Complexity and Change

Abstract: This paper presents a study of complex society and its relationship to project management. The complex society is characterised by open systems, chaos, self organisation and interdependence. Accelerated change drives instability and chaos following an autocatalytic process. The conventional project management approach assumes a world of order and a predictable environment in which one can set and deliver a clear set of goals in a defined manner. The traditional approach is open to challenge. The author argues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(69 citation statements)
references
References 3 publications
1
63
0
5
Order By: Relevance
“…Social complexity referred to (again) actors involved, their interests and the risks and consequences of the project in relation to its environment. Also other studies indicated the environment as an important contributor to project complexity (Jaafari 2003;Xia and Lee 2005;Mason 2007). Also Antoniadis et al (2011) favour an approach in which complexity is considered broader than just technical complexity: they showed the importance of recognizing socio-organizational complexity.…”
Section: Concepts Of Project Complexitymentioning
confidence: 95%
See 1 more Smart Citation
“…Social complexity referred to (again) actors involved, their interests and the risks and consequences of the project in relation to its environment. Also other studies indicated the environment as an important contributor to project complexity (Jaafari 2003;Xia and Lee 2005;Mason 2007). Also Antoniadis et al (2011) favour an approach in which complexity is considered broader than just technical complexity: they showed the importance of recognizing socio-organizational complexity.…”
Section: Concepts Of Project Complexitymentioning
confidence: 95%
“…Whereas the authors mentioned above focused on "structural complexity" and "uncertainty", also softer aspects and influences from the environment are assumed to influence project complexity (De Bruijn et al 1996;Jaafari 2003;Geraldi and Adlbrecht 2007). Geraldi further developed the Williams concept earlier described and distinguished the complexity of fact and the complexity of faith (Geraldi and Adlbrecht 2007) as well as the complexity of interaction.…”
Section: Concepts Of Project Complexitymentioning
confidence: 99%
“…The methods for managing risks have been widely discussed in the literature on projects (Jaafari, 2003;Kwak & Stoddard, 2004;Lyons & Skitmore, 2004;Kerzner, 2009;Zwikael & Ahn, 2011;PMI, 2013). Within this framework, Raz & Michael (2001) established a Ranking with the most contributory practices to the management, relating them to the processes of identification, assessment, response, monitoring, control, and background.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…As the sources of complexity are pronounced to be various, dynamic, and uncertain, there is no consensus on complexity [13][14][15]. The difficulty in defining complexity can be minimised through the identification of its key drivers, although, defining those key drivers is not easier, either in the field of project management or in other domains.…”
Section: What Is Project Complexity?mentioning
confidence: 99%